2001
DOI: 10.1136/jme.27.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Artificial nutrition and hydration in the patient with advanced dementia: is withholding treatment compatible with traditional Judaism?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The Conservative Movement's Committee on Jewish Law and Standards adopted a somewhat dissimilar view in classifying artificial nutrition and hydration as medicine, permitting their removal where there is not likely to be any reasonable prospect for recovery at the end of life (Zahedi et al 2007). It is suggested that when the decision is made to discontinue artificial nutrition and hydration, the focus of communication should be on ''what will be done to demonstrate respect for the patient, rather than on emphasising what will be withdrawn or withheld'' (Gillick 2001;Loike et al 2010). With regard to palliative sedation, there is a general agreement in Jewish law that this is permitted in spite of the risk that the administration of such drugs may shorten life, based on the principle of double effect (Bülow et al 2008;Loike et al 2010).…”
Section: The Jewish Perspectivementioning
confidence: 99%
“…The Conservative Movement's Committee on Jewish Law and Standards adopted a somewhat dissimilar view in classifying artificial nutrition and hydration as medicine, permitting their removal where there is not likely to be any reasonable prospect for recovery at the end of life (Zahedi et al 2007). It is suggested that when the decision is made to discontinue artificial nutrition and hydration, the focus of communication should be on ''what will be done to demonstrate respect for the patient, rather than on emphasising what will be withdrawn or withheld'' (Gillick 2001;Loike et al 2010). With regard to palliative sedation, there is a general agreement in Jewish law that this is permitted in spite of the risk that the administration of such drugs may shorten life, based on the principle of double effect (Bülow et al 2008;Loike et al 2010).…”
Section: The Jewish Perspectivementioning
confidence: 99%
“…16 When the decision is made to discontinue artificial nutrition and hydration, the focus of communication should be on ''what will be done to demonstrate respect for the patient, rather than on emphasizing what will be withdrawn or withheld.'' 14,17 …”
Section: Nutrition and Hydrationmentioning
confidence: 98%
“…Initial item development The development of the initial list of potential checklist items was based on a review of the literature related to the mechanisms and concept of thirst in the elderly (Gillick, 2001;Kenney & Chiu, 2001;Phillips et al, 1991) and on the Cohen-Mansfield Agitation Inventory (Cohen-Mansfield, 1991;Lin, Kao, Tzeng, & Lin, 2007). After the item pool was established, semistructured individual interviews were conducted with 10 registered nurses with at least 2 years of experience caring for patients with dementia.…”
Section: Phase Lmentioning
confidence: 99%
“…It is also worth noting that older patients with advanced dementia (PwAD) often lose interest or desire for food and drink and have problems with the coordinated processes necessary for swallowing, making it difficult to experience thirst (Gillick, 2001). When feeling thirsty, as mentioned earlier, PwAD who cannot express their needs verbally often express their need for fluids using certain behaviors and psychological symptoms.…”
Section: Introductionmentioning
confidence: 97%